“Smells fishy”: Exploring Community Reactions to Aquaculture in Frenchman Bay, Maine - Gurney, Gabriella; Rickard, Laura (Maine Policy Review, 2024)
The authors of this research brief conducted a series of qualitative interviews with people in the Frenchman Bay watershed in Maine concerning a proposal for an aquaculture facility in the bay. Based on the interviews, they identified emergent themes regarding place attachments to Frenchman Bay and sense of place. Scale was identified as an umbrella concept encompassing the other themes, including perceived environmental and community risks and drawbacks; aesthetic, historical, and recreation-based place attachments; and concerns intersecting with adjacent marine tensions such as state licensing processes and the shifting of traditional working waterfronts to tourism-based economies. The study highlights several implications for aquaculture policy in Maine.
Keywords: Atlantic salmon; fish hatchery; finfish aquaculture; sense of place